Memorial dedicated to Robert Ashmead Billamore - Ghosh, Ayan (2023)
Memorial dedicated to Robert Ashmead Billamore, Lieutenant and Adjutant of the First Battalion of the 10th Regiment of the Bombay Native Infantry. He died at Jalna on 7 May 1818, during the Third Anglo-Maratha War, which ended Peshwa rule in the Deccan. His late father, Robert Billamore, had served as a captain in the East India Company Marine Corps.